Answer:
3x^2-x+5.2f\left(-3\right)-f\left(4\right) =
3x^2-x-19.6f
Step-by-step explanation:
3x^2-x+5.2f\left(-3\right)-f\left(4\right)
=3x^2-x-5.2f\cdot \:3-f\cdot \:4
=3x^2-x-15.6f-4f
=3x^2-x-19.6f
Answer:
23
Step-by-step explanation:
6x3=18
18+5=23
Answer:
2x +3x =7-13=4+8
Step-by-step explanation:
5x= -6= 12
After solving
we get ![p](https://tex.z-dn.net/?f=p%3C%5Cfrac%7B3%7D%7B2%7D)
Step-by-step explanation:
We need to solve
![4p + 2 < 2p + 5](https://tex.z-dn.net/?f=4p%20%2B%202%20%3C%202p%20%2B%205)
Solving
![4p + 2 < 2p + 5](https://tex.z-dn.net/?f=4p%20%2B%202%20%3C%202p%20%2B%205)
Subtract 2 from both sides:
![4p + 2-2 < 2p + 5-2\\4p](https://tex.z-dn.net/?f=4p%20%2B%202-2%20%3C%202p%20%2B%205-2%5C%5C4p%3C2p%2B3)
Subtract 2p from both sides
![4p](https://tex.z-dn.net/?f=4p%3C2p%2B3%5C%5C4p-2p%3C2p-2p%2B3%5C%5C2p%3C3)
Divide both sides by 2p
![\frac{2p}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B2p%7D%7B2%7D%3C%5Cfrac%7B3%7D%7B2%7D%5C%5Cp%3C%5Cfrac%7B3%7D%7B2%7D)
So, after solving
we get ![p](https://tex.z-dn.net/?f=p%3C%5Cfrac%7B3%7D%7B2%7D)
Keywords: Inequality
Learn more about inequality at:
#learnwithBrainly